ANALYSIS OF THE DEVELOPMENT OF HADITH TRENDS IN INDONESIA (Literature Study in The Journal of Al-Qur'an and Hadith Studies UIN Sunan Kalijaga Yogyakarta, 2022–2024) - Sari, Rusita (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
This study analyzes the phenomenon of hadith contained in the journal of Qur'anic Sciences and Hadith Studies of UIN Sunan Kalijaga Yogyakarta Year 2022-2024, namely how hadith is understood, applied, and debated in various aspects of Muslim life. This study covers the meaning of hadith in Islamic art through hermeneutic, criticism and living hadith approaches spread in various regions in Indonesia. The results show that hadith not only functions as a normative text, but also adapts to modern social, cultural and technological contexts, making it an integral part of contemporary Islamic dynamics.